Prevalence and Patient Outcomes of Adult Primary Hypercholesterolemia and Dyslipidemia in the UK: Longitudinal Retrospective Study Using a Primary Care Dataset from 2009 to 2019 - Bilitou A; Were J; Farrer A; Rabe A; Ming SWY; Haq I; Dunton K (Dove Medical Press, 2022)
Aikaterini Bilitou,1 John Were,2 Archie Farrer,2 Adrian Rabe,2,3 Simon Wan Yau Ming,2 Inaam Haq,1 Kyle Dunton4 1Daiichi Sankyo Europe GmbH, Munich, Bayern, Germany; 2Health iQ Ltd, London, UK; 3Imperial College London, London, UK; 4Daiichi Sankyo UK Ltd, Uxbridge Business Park, Uxbridge, UKCorrespondence: Aikaterini Bilitou, Health Economics and Outcomes Research, Daiichi Sankyo Europe GmbH, Zielstattstrasse 48, Munich, 81379, Bayern, Germany, Tel +49 897 808802, Email aikaterini.bilitou@daiichi-sankyo.euBackground: Guidelines for the management of dyslipidemias recommend intensive low-density lipoprotein (LDL-C) control through lifestyle advice and lipid-lowering drugs to reduce the risk of cardiovascular disease (CVD).Objective: This retrospective study aimed to characterize the adult primary care population with primary hypercholesterolemia (PH)/mixed dyslipidemia (MD).Methods: Data on adults with PH/MD between 1 January 2009 and 31 December 2019 in the UK were extracted from linked primary Clinical Practice Research Datalink (CPRD) and secondary care (Hospital Episode Statistics) datasets and analyzed.Results: A total of 279,221 patients met the inclusion criteria. Mean follow-up was 8.6 years. Crude prevalence of PH/MD increased from 13.5% in 2009 to 23.5% by 2019. The incidence decreased from 176 to 49 per 100,000 population. Mean age of the cohort was 58 years, baseline LDL-C was 4.32 mmol/L, 19.6% had atherosclerotic CVD, 30.1% diabetes, and 8.5% heterozygous familial hypercholesterolemia. Estimated LDL-C reductions of 40% and 50% were achieved in 2.6% and 2.3% of patients, respectively. Most received moderate-intensity statins as monotherapy (62.4%); high-intensity statins were used less frequently (24.3% as initial treatment). Less than 10% of patients received ezetimibe plus statins of different intensities.Conclusion: The prevalence of dyslipidemia doubled between 2009 and 2019, likely due to more systematic identification of PH/MD. A large proportion of patients with PH/MD are of high and very high CV risk, remain suboptimally treated in terms of lipid lowering, and may experience CV events with associated non-negligible clinical and economic sequelae. Despite intensive LDL-C-lowering recommendations, these do not translate in clinical practice to the wider population.Keywords: lipid management, atherosclerosis, cardiovascular disease, NICE guidelines